2015
DOI: 10.1097/wnr.0000000000000413
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of morphology, electrophysiology, and central projections of two sensilla styloconica in Helicoverpa assulta larvae

Abstract: The medial and lateral styloconic sensilla, constituting the main taste organs of lepidopterous caterpillars, were investigated in the oligophagous species, Helicoverpa assulta (Guenée) (Lepidoptera: Noctuidae). In this paper, the two sensilla were morphologically and physiologically characterized by scanning electron microscopy and tip recordings, respectively. The central projections of their respective sensory neurons were mapped by anterograde staining experiments combined with confocal laser scanning micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The plasticity of feeding behavior induced by dietary exposure could be mediated by peripheral taste sensitivity, gustatory transduction pathways, centrifugal control by the central gustatory system or post-ingestive mechanisms 31 , 33 , 55 , 56 . The central projections of gustatory neurons in the sensilla styloconica displayed similar patterns in caterpillars of the two Helicoverpa species but differed in the distributions of neural branches in the subesophageal ganglion 57 , 58 . Molecular study using cDNA microarrays showed that the specialist Manduca sexta regulated transcripts in a diet-specific manner, while the generalist Heliothis virescens regulated a similar suite of transcripts across all diet types, suggesting that specialists are better adapted than generalist herbivores 59 .…”
Section: Discussionmentioning
confidence: 88%
“…The plasticity of feeding behavior induced by dietary exposure could be mediated by peripheral taste sensitivity, gustatory transduction pathways, centrifugal control by the central gustatory system or post-ingestive mechanisms 31 , 33 , 55 , 56 . The central projections of gustatory neurons in the sensilla styloconica displayed similar patterns in caterpillars of the two Helicoverpa species but differed in the distributions of neural branches in the subesophageal ganglion 57 , 58 . Molecular study using cDNA microarrays showed that the specialist Manduca sexta regulated transcripts in a diet-specific manner, while the generalist Heliothis virescens regulated a similar suite of transcripts across all diet types, suggesting that specialists are better adapted than generalist herbivores 59 .…”
Section: Discussionmentioning
confidence: 88%
“…These results suggested that EolbCXE7 and EoblCXE13 might function in the E. obliqua olfactory system; however, whether the functions of EolbCXE7 and EoblCXE13 resemble those of their orthologs SlittCXE7 and SexiCXE13 as candidate ODEs in the degradation of ( Z )-3-hexenyl acetate remains to be further confirmed. Additionally, EoblCXE7 and EoblCXE13 were highly expressed at Sst, a putative gustatory sensillum in lepidopteran species (Zenker et al, 2011 ; Tang et al, 2015 ), and we therefore cannot rule out the possibility that both of these EoblCXEs might function in the gustatory system.…”
Section: Discussionmentioning
confidence: 92%
“…Outside Drosophila , gustatory projections of insect larvae have been described for several species of Lepidoptera ( Manduca : Kent & Hildebrand, ; Antheraea : Asaoka, ; Helicoverpa : Tang, Hong, Cao, Yan, & Zhao, ; Tang et al, ). Similar to dipteran larvae, head appendages are much smaller in lepidopteran larvae than in adults.…”
Section: Discussionmentioning
confidence: 99%